2016
DOI: 10.1097/md.0000000000003111
|View full text |Cite
|
Sign up to set email alerts
|

A Case Report of Esophageal Bronchogenic Cyst and Review of the Literature With an Emphasis on Endoscopic Ultrasonography Appearance

Abstract: Esophageal bronchogenic cysts are extremely rare. Here we report a more rare type of both presence of intra- and paraesophageal bronchogenic cyst that was safely removed via surgical resection. A 31-year-old male patient with space-occupying lesions in the mediastinum suddenly presented with persistent chest pain for 2 days and then transferred to dysphagia >1 week. Preoperative diagnosis is difficult. Endoscopic ultrasonography (EUS) showed a hypoechoic cystic-solid mass arising from the muscularis propria an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 23 publications
2
16
0
2
Order By: Relevance
“…We did not see any double muscle layer, classically observed in duplication cysts. Moreover, we observed an apical immunostaining of CA‐125 and CA19.9 that has already been reported in esophageal bronchogenic cyst …”
supporting
confidence: 83%
“…We did not see any double muscle layer, classically observed in duplication cysts. Moreover, we observed an apical immunostaining of CA‐125 and CA19.9 that has already been reported in esophageal bronchogenic cyst …”
supporting
confidence: 83%
“…Reports of high levels of both CA199 and CA125 are extremely rare. 16 , 33 , 38 In the present case, abnormal levels of CA199 and CA125 were also detected in the serum and the cyst sections, and the elevated CA199 and CA125 levels decreased to a normal range postoperatively. These findings suggested that the serum levels of CA199 and CA125 were partly correlated with epithelial cell secretion from the esophageal BC in our patient.…”
Section: Discussionsupporting
confidence: 61%
“…Preoperative serum levels of CA 19-9 were also elevated (albeit to a much lesser extent) in patients with bronchogenic cysts in the report by Han et al [ 10 ] (156.3 U/mL). CA 19-9 levels returned to normal following resection of the cyst in our study; postoperative CA 19-9 levels were not measured in the study by Han et al [ 10 ]…”
Section: Discussionmentioning
confidence: 86%